2017
DOI: 10.1186/s12864-017-3944-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide signals of positive selection in strongylocentrotid sea urchins

Abstract: BackgroundComparative genomics studies investigating the signals of positive selection among groups of closely related species are still rare and limited in taxonomic breadth. Such studies show great promise in advancing our knowledge about the proportion and the identity of genes experiencing diversifying selection. However, methodological challenges have led to high levels of false positives in past studies. Here, we use the well-annotated genome of the purple sea urchin, Strongylocentrotus purpuratus, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 102 publications
(146 reference statements)
0
27
1
Order By: Relevance
“…We have shown that over deep evolutionary timescales, CCTα displays recurrent signatures of accelerated evolution and structural adaptation in transition from shallow- to deep-sea habitats in brittle stars. This contrasts with previous findings on sea urchins where, CCTε—but not the other subunits—showed signatures of positive section, yet not in the two deep-sea species included in the work ( Kober and Pogson 2017 ). A functional equivalent of the eukaryotic chaperonin CCT in bacteria is the chaperonin complex GroEL/GroES ( Gupta 1990 ; Mayhew et al.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We have shown that over deep evolutionary timescales, CCTα displays recurrent signatures of accelerated evolution and structural adaptation in transition from shallow- to deep-sea habitats in brittle stars. This contrasts with previous findings on sea urchins where, CCTε—but not the other subunits—showed signatures of positive section, yet not in the two deep-sea species included in the work ( Kober and Pogson 2017 ). A functional equivalent of the eukaryotic chaperonin CCT in bacteria is the chaperonin complex GroEL/GroES ( Gupta 1990 ; Mayhew et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Patterns of positive selection have been investigated to uncover genes underlying adaptation to specific environments, including the deep sea, in nonmodel species ( Oliver et al. 2010 ; Kober and Pogson 2017 ; Sun et al. 2017 ; Weber et al.…”
Section: Introductionmentioning
confidence: 99%
“…2005 ; Kosiol et al . 2008 ; Kober and Pogson 2017 ), and suggests limited power to detect positive selection in M. galloprovincialis and M. edulis ( fig. 1 ) within this data.…”
Section: Resultsmentioning
confidence: 99%
“…A consensus alignment for each species was generated for each gene following the methods described in Kober and Pogson (2017) . Unless specified, we performed data processing using BioPerl ( Stajich etal.…”
Section: Methodsmentioning
confidence: 99%
“…The Sea Urchin Genome Project has also assembled genome sequences from two additional sea urchins, a sea star, sea cucumber, and brittle star ( ). Four high-quality and three less complete genome assemblies, as well as high coverage, unassembled whole genome sequencing reads are available from other echinoderm species ( 35 38 ). In total, the NCBI Short Read Archive hosts 206 projects in 75 echinoderm species that cover all five classes as of this writing.…”
Section: A Wealth Of Echinoderm Genomic Resources Is Availablementioning
confidence: 99%